Attic Hatch Model Implementation Using the Bondgraph - Zulkifli Hidayat; Hany Ferdinando (Jurnal Teknik Mesin (Sinta 3), 2004)
The Bondgraph had been used widely in building and simulating a model. This paper solves a problem in an attic hatch (planar mechanism problem) using Bondgraph approach. Planar mechanisms are idealized systems that can translate and rotate in one plane. In the same way as linear translation or uni-axial rotation, planar motions can be considered as a special case of spatial motions of mechanisms. In the attic hatch system, people have to push with lot of power to open it. Then came up an idea to add a mass-pulley mechanism in order to open and close it easily. Before implementing this idea, it needs to simulate it first, because it needs to adjust many parameter combinations. This will also prevent someone to make unnecessary hole while implementing this idea (such as trial and error). This paper only dealt with building and simulating this idea, not going further in the real implementation. The simulation result shows that several parameters should be chosen carefully in order to achieve the final goal, i.e. to open the hatch easily and fast. The 20-Sim simulation package is used to verify the model. Abstract in Bahasa Indonesia : Bondgraph sudah dipergunakan secara luas untuk mensimulasikan sebuah model dari plant. Makalah ini akan membahas permasalahan yang terjadi dalam membuat sebuah attic hatch (pintu ke atap yang biasanya terdapat di rumah-rumah Eropa) dengan menggunakan bondgraph. Attic hatch merupakan suatu permasalahan dalam planar mechanism. Planar mechanism ada system ideal yang dapat bertranslasi dan berotasi dalam satu bidang datar. Seperti pada translasi linier atau rotasi pada satu sumbu, gerakan planar dapat digolongkan sebaagai kasus khusus dalam mekanik. Pada attic hatch,orang harus mendorong pintu untuk membukanya. Sehingga muncul suatu ide untuk menambahkan katrol dan beban untuk memudahkan proses buka dan tutupnya. Untuk menambahkan katrol dan beban ini, perlu dilakukan suatu simulasi untuk menghindari pembuatan lobang yang tidak perlu. Makalah ini hanya membahas simulasi dari sistemnya tanpa memasukkan implementasi secara nyata. Dari hasil simulasi, didapatkan bahwa beberapa parameter harus dipilih secara hati-hati untuk dapat membuka dan menutup pintu dengan mudah. Dalam simulasi ini dipergunakan software 20-Sim. Bond graph, simulation, 20-Sim. Kata kunci: bondgraph, simulasi, 20-Sim